Utilizing classical scaling for fault identification based on continuous-based process - Mira Syahirah, Abd Wahit (2013)
This study is about to develop a new method on Fault Identification using Classical Scaling. Process Monitoring is from Statistical Process Control (SPC), the statistical tool which used of statistical methods and to control of a process, by repeated sampling measurements or to predict results. It also help to determine whether the process is working properly or not. This Statistical Process Control (SPC) will forms charts with data (control charts) to shown the result. This study will develop the normal Multivariate Statistical Process Monitoring (MSPM). The data will be run as the normal Multivariate Statistical Process Monitoring (MSPM). So from the technique that used in this study such as Principal Component Analysis, Statistical Process Control and Multivariate Statistical Process Monitoring (MSPM), this study will be develop which the most faster technique that will be detecting the fault in the system used.